I am an Afrikaner Woman - Magona, Sindiwe (Multilingual Margins: A journal of multilingualism from the periphery, 2017)
In the run up to the first truly democratic elections in South Africa, the Afrikaner women issued a heartfelt cry: What have you done in our name? Did Black women understand the question? Twenty years later, many a black-black woman, â€œBantuâ€ in the terminology of yesteryear, have begun to feel the anguish of their Afrikaner Sisters. Indeed, I am become the Afrikaner woman of yesteryear - Guilty by Association. The lesson? Power disempowers women and yet, in the final analysis, we are all held accountable for the ills of society. In essence, there is no â€˜otherâ€™